PENERAPAN DIGITALISASI KEUANGAN PADA MAJELIS TA'LIM ROUDHOTUNNISA BERBASIS APLIKASI SRIBUU UNTUK PENINGKATAN EFISIENSI ADMINISTRASI - Trias Baiti Jannati; Elma Ermawati; Khairani Azqya; Raesita Raesita; Eka Wahyu Winingsih; Prisila Damayanty (ASOSIASI IDEBAHASA KEPRI, 2026)
This community service activity aims to improve the efficiency of financial administration at Majelis Ta’lim Roudhotunnisa, located in Tanjung Barat Subdistrict, South Jakarta, through the implementation of financial digitalization using the Sribuu application. The main problem faced by the partner institution was the use of a manual financial recording system based on ledger books, which was inefficient, prone to errors, and made financial data recapitulation difficult. The community service program was conducted in December 2025 and involved two core administrators, namely the chairperson and the treasurer, as well as 35 members of the Majelis Ta’lim. The implementation methods included socialization on the importance of financial recordkeeping, training on the use of the Sribuu application, hands-on assistance, and monitoring and evaluation. The results indicate that the administrators were able to record income and expenses digitally, the time required for financial recording became shorter, and financial data were more organized and easier to recapitulate. In addition, there was an improvement in the administrators’ understanding of systematic and accountable financial management. The implementation of financial digitalization using the Sribuu application is expected to support transparency and sustainability in the financial management of community organizations.